The Impact of Shopee PayLater on Students' Consumptive Behavior: Between Convenience and Traps - Antonius Felix; Vindis Vindis; Yulianto Yulianto; Rivaldo Lyem Tratabofa Hutasoit; Fanuel Alexander; Julius Sutrisno (Universitas Bunda Mulia, 2024)
This study aims to examine the in-depth impact of using the Shopee PayLater feature on students' consumptive behavior. Through in-depth interviews with a number of active Shopee PayLater users, this study reveals a significant correlation between the use of this feature and increased consumptive behavior. The ease of access, attractive promotions, and payment flexibility offered by Shopee PayLater are the main attractions for students.The research findings show that students tend to use Shopee PayLater to meet urgent needs, such as buying books, stationery, or other daily necessities. However, this easy access also triggers uncontrolled consumptive behavior, such as purchasing unnecessary items or making impulsive purchases driven by promotions. In addition, the payment flexibility offered by Shopee PayLater can make students feel more comfortable with debt and postpone payments, potentially leading to financial problems in the future.This study also identifies other factors that influence the consumptive behavior of Shopee PayLater-using students, such as peer influence, consumptive lifestyles, and financial literacy levels. Students with a more consumptive social environment are more likely to be influenced to use Shopee PayLater excessively. Moreover, students with low financial literacy levels tend to have difficulty managing their finances and are more susceptible to the temptation to make impulsive purchases.Based on the results of this study, it can be concluded that Shopee PayLater has a complex impact on students' consumptive behavior. On the one hand, this feature provides convenience and flexibility that is much needed, especially for students with financial constraints. On the other hand, this ease can also trigger unhealthy consumptive behavior if not managed well. Therefore, it is important for students to have adequate financial literacy to be able to use this feature wisely and avoid financial problems in the future.